An engineered vaccine of the Plasmodium vivax Duffy binding protein enhances induction of broadly neutralizing antibodies. Issue 1 (December 2017) - Ntumngia, Francis; Pires, Camilla; Barnes, Samantha; George, Miriam; Thomson-Luque, Richard; Kano, Flora; Alves, Jessica; Urusova, Darya; Pereira, Dhelio; Tolia, Niraj; King, Christopher; Carvalho, Luzia; et al.
Abstract Plasmodium vivax invasion into human reticulocytes is a complex process. The Duffy binding protein (DBP) dimerization with its cognate receptor is vital for junction formation in the invasion process. Due to its functional importance, DBP is considered a prime vaccine candidate, but variation in B-cell epitopes at the dimer interface of DBP leads to induction of strain-limited immunity. We believe that the polymorphic residues tend to divert immune responses away from functionally conserved epitopes important for receptor binding or DBP dimerization. As a proof of concept, we engineered the vaccine DEKnull to ablate the dominant Bc epitope to partially overcome strain-specific immune antibody responses. Additional surface engineering on the next generation immunogen, DEKnull-2, provides an immunogenicity breakthrough to conserved protective epitopes. DEKnull-2 elicits a stronger broadly neutralizing response and reactivity with long-term persistent antibody responses of acquired natural immunity. By using novel engineered DBP immunogens, we validate that the prime targets of protective immunity are conformational epitopes at the dimer interface. These successful results indicate a potential approach that can be used generally to improve efficacy of other malaria vaccine candidates.